The effect of age and gender on heart rate variability after endurance training - Carter, J. B.; Banister, E. W.; Blaber, A. P. (Medicine & Science in Sports & Exercise, 2003)
PURPOSE: This research investigated the age and gender differences in cardiovascular adaptation to a standardized/quantified endurance-training program that included two taper periods. METHODS: The latter was analyzed from spectral analysis of electrocardiogram records of heart rate variability (HRV) at rest in groups of young (19-21 yr) and middle aged (40-45 yr), mixed gender groups (6 males and 6 females), pre- and poststandardized training. All subjects were recreational runners who completed the same 12-wk running program. Before, and subsequent to training, HRV was measured during supine rest and submaximal cycling. RESULTS: There was a significant decrease in heart rate both at rest (2.7 +/- 0.45 beats x min-1) and during submaximal exercise (8.1 +/- 0.67 beats x min-1) in both age groups after training. After training, total spectral power increased (560.7 +/- 308.9 ms2), as well as high-frequency power (362.3 +/- 405.5 ms2), in both age groups at rest. The young group showed a greater increase in total power (849.0 +/- 308.7 ms2) after the training program. CONCLUSION: It is concluded that a well-designed 12-wk endurance-training program will decrease resting and submaximal heart rate in both younger and older adults. The significant increase in HRV, total power, and high-frequency power in all groups after endurance training indicates that HRV measurement appears to provide an effective, noninvasive assessment of cardiovascular adaptation to aerobic training.